Phenotypic and genotypic analysis of patients with congenital factor VII deficiency in a multicenter study in Thailand - Ampaiwan Chuansumrit; Surapan Parapakpenjune; Rungrote Natesirinilkul; Patcharee Komvilaisak; Werasak Sasanakul; Nongnuch Sirachainan; Anchalee Aramthienthamrong; Chorthip Wattanasutthipong; Kittima Kanchanakumhan; Kunrada Inthawong; Montana Chantaraniyom; Naonpan Pongpaothai; et al. (Elsevier, 2022)
Objective: The phenotypic and genotypic analysis of patients with congenital factor VII deficiency were retrospectively conducted. Methods: The study included 26 patients defined as severe (n = 25) and moderate (n = 1) degree by FVII <10% and 10-20%, respectively. Results: The diagnosis of factor VII deficiency was based on an isolated prolonged prothrombin time with subsequent factor assay. The median age of first bleed was 7 days (IQR 2-11.2 days). Central nervous system and gastrointestinal tract bleeding were found among all patients with severe degree. Patients with FVII <1-3% exhibited serious bleeding during the first week to the first month of life while patients with FVII >3% did not exhibit serious spontaneous bleeding. The initial bleeding episodes were controlled by administering fresh frozen plasma (FFP) and switched to factor concentrates among a few patients upon definite diagnosis. Subsequent prophylaxis was provided to patients with initial severe bleeding manifestation using FFP (15 ml/kg) 2-3 times weekly or recombinant factor VIIa (90 μg/kg) twice weekly. Genotypic analysis revealed homozygous or double heterozygous mutations among all patients except one patient with heterozygous mutation combined with homozygous polymorphism at codon 413 of G to A substitution (AA) at exon 8 of the FVII gene. The FVII gene mutation was commonly found at IVS6+1G > T (38.3%), followed by p.K376 X (19.2%) and IVS2+2T > C (17.0%). The case fatality rate was 19.2% (5/26) among patients with severe degree. Conclusion: Early diagnosis and appropriate management of congenital factor VII deficiency is essential for favorable outcomes.